Obesity in COVID-19 era, implications for mechanisms, comorbidities, and prognosis: a review and meta-analysis - Aghili, Seyed Morsal Mosallami; Ebrahimpur, Mahbube; Arjmand, Babak; Shadman, Zhaleh; Pejman Sani, Mahnaz; Qorbani, Mostafa; Larijani, Bagher; Payab, Moloud (International Journal of Obesity, 2021)
Recent studies have shown that obesity is associated with the severity of coronavirus disease (COVID-19). We reviewed clinical studies to clarify the obesity relationship with COVID-19 severity, comorbidities, and discussing possible mechanisms. The electronic databases, including Web of Science, PubMed, Scopus, and Google Scholar, were searched and all studies conducted on COVID-19 and obesity were reviewed. All studies were independently screened by reviewers based on their titles and abstracts. Forty relevant articles were selected, and their full texts were reviewed. Obesity affects the respiratory and immune systems through various mechanisms. Cytokine and adipokine secretion from adipose tissue leads to a pro-inflammatory state in obese patients, predisposing them to thrombosis, incoordination of innate and adaptive immune responses, inadequate antibody response, and cytokine storm. Obese patients had a longer virus shedding. Obesity is associated with other comorbidities such as hypertension, cardiovascular diseases, diabetes mellitus, and vitamin D deficiency. Hospitalization, intensive care unit admission, mechanical ventilation, and even mortality in obese patients were higher than normal-weight patients. Obesity could alter the direction of severe COVID-19 symptoms to younger individuals. Reduced physical activity, unhealthy eating habits and, more stress and fear experienced during the COVID-19 pandemic may result in more weight gain and obesity. Obesity should be considered as an independent risk factor for the severity of COVID-19. Paying more attention to preventing weight gain in obese patients with COVID-19 infection in early levels of disease is crucial during this pandemic.